Shelf life improvement of idli batter by addition of mustard essential oil as bio-preservative - Regubalan, Baburaj (J Food Sci Technol, 2018)
Idli is one of the most popular naturally fermented breakfast food. In this study, essential oils have been screened for their minimal inhibitory activity against selected lactic acid bacteria (LAB) and yeast strain associated with idli batter fermentation and to identify the best potential bio preservative to preserve the idli batter. Mustard essential oil was found to be the best bio-preservative which showed a biocidal effect at 80 ppm against LAB strains and at 40 ppm against Candida versatilis. The efficacy of mustard essential oil incorporated in the idli batter at 0.1% (w/w) was evaluated by measuring the titratable acidity, pH, viscosity, batter volume, microbial count of idli batter as well as sensory parameters of idli prepared from preserved batter stored at 4 and 30 °C. Unfavorable changes in acidity, batter volume and whey separation of idli batter containing mustard oil were significantly reduced, which resulted in a reduction of sour taste and improved texture of idli. The growth of yeast and LAB was retarded evidenced by decreased microbial counts than control batter, which delayed the deterioration of the batter under both storage conditions. The addition of 0.1% mustard essential oil in the optimally fermented idli batter extended its shelf life to 5 days when stored at 30 °C and 30 days at 4 °C. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13197-018-3247-2) contains supplementary material, which is available to authorized users.